Gender Inequality and Economic Growth - Cuberes, David (Washington, DC: World Bank, 2012)
Gender inequality is a pervasive feature in many developing countries. The gaps between male and female outcomes and opportunities are present in several dimensions: education, earnings, occupation, access to formal employment, access to managerial positions, access to productive inputs, political representation, or bargaining power inside the household. These gaps are particularly dramatic in developing countries. Dollar and Gatti (1999) estimate the following education gap in schooling: in the poorest quartile of countries in 1990, only 5% of adult women had any secondary education, one-half of the level for men. In the richest quartile, on the other hand, 51% of adult women had at least some secondary education, 88% of the level for men. On the other hand, the gaps in employment and pay are closing much faster in developing countries than they did in industrialized ones (Tzannatos, 1999), but the prevalence of gender inequality is still sizable, especially in South Asia and the Middle East and North Africa (Klasen and Lamanna, 2009). Moreover, the majority of family workers are women and, often unpaid. Women are also underrepresented among top positions in most countries: even in the most developed ones, the average incidence of females among managers is less than 30% (World Bank 2001). The data also shows that women are typically employed in a reduced number of industrial sectors: more than two-thirds of the global labor force in garment production is females and 1/5th of the total female labor force is in manufacturing.